A biorefinery approach to the biomass of the seaweed Undaria pinnatifida (Harvey Suringar, 1873): obtaining phlorotannins-enriched extracts for wound healing - Ferreira, Carolina A. M. (2021)
Brown seaweeds are recognized sources of compounds with a wide range of properties and applications. Within these compounds, phlorotannins are known to possess several bioactivities (e.g., antioxidant, anti-inflammatory, and antimicrobial) with potential to improve wound healing. To obtain phlorotannins enriched extracts from Undaria pinnatifida, a biorefinery was set using lowcost industry-friendly methodologies, such as sequential solid–liquid extraction and liquid–liquid extraction. The obtained extracts were screened for their antioxidant and antimicrobial activity against five common wound pathogens and for their anti-inflammatory potential. The ethanolic wash fraction (wE100) had the highest antioxidant activity (114.61 +- 10.04 mmol mg-1 extract by Diphenyl-1-picrylhydrazyl (DPPH) and 6.56 +-1.13mMeq. Fe II mg-1 extract by and Ferric Reducing Antioxidant Power (FRAP)), acting efficiently against Gram-negative (Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus) bacteria, and showing a nitric oxide production inhibition over 47% when used at 0.01 ug mL-1. NMR and FTIR chemical characterization suggested that phlorotannins are present. Obtained fraction wE100 proved to be a promising candidate for further inclusion as wound healing agents, while the remaining fractions analyzed are potential sources for other biotechnological applications, giving emphasis to a biorefinery and circular economy framework to add value to this seaweed and the industry.